(untitled) (Journal of the College of Basic Education, 2022)
In this research, the ceramic method was used to prepare ferrite (Cu 1-x Zn x Fe 2 O 4) with The composition of the spinel, where x represents the percentage of zinc in the ferrite material, and the prepared ferrite was studied RAM absorbent material and waveguide technology was used. to study the absorption of this material for microwaves at the X-band. band with a frequency range GH z (8-12) by calculating the value of the reflection coefficient and the attenuation coefficient The reflectivity and absorbance as a function of frequency within the X-band, with an increase of (0.25). GH z and measuring the standing wave voltage ratio V SWR within the waveguide